Chinese Medicinal Formula (MHGWT) for Relieving Diabetic Neuropathic Pain: A Randomized, Double-Blind, Placebo-Controlled Trial. (25th August 2013) - Tsai, Chia-I; Li, Tsai-Chung; Chang, Ming-Hong; Lin, Shih-Yi; Lee, I-Te; Lee, Cheng-Hung; Wang, Tzu-Yuan; Su, Yi-Chang
Abstract : Objective . To investigate the effects of modified Hungqi Guizhi Wuwu Tang (MHGWT), a formula that comprises Chinese medicinal herbs, in relieving neuropathic pain in diabetics. Method . Between March 2008 and April 2009, 112 participants were randomly assigned to either the MHGWT group, whose members received MHGWT (n = 56 ), or the control group, whose members received a placebo (n = 56 ). Diabetic neuropathic pain (DNP) was rated using the 15-item Short-Form Brief Pain Inventory (SF-BPI), the 17-item Short-Form McGill Pain Questionnaire (SF-MPQ), the 13-item Modified Michigan Neuropathy Screening Instrument (MMNSI), and the 36-item "SF-36." Nerve conduction studies (NCSs) were performed before and after treatment. Results . After 12 weeks of treatment, the SF-MPQ and SF-BPI scores of the MHGWT group were significantly (P < 0.05 ) reduced and a significant difference between the groups was observed (P < 0.05 ). The levels of NCS in the MHGWT group were nonsignificantly (P > 0.05 ) reduced, and no significant difference in NCS level was observed between the groups (P > 0.05 ). Conclusions . MHGWT shows promise in relieving DNP and deserves further investigation.